A standartized research protocol for platelet-rich plasma (PRP) preparation in rats - Messora, Michel Reis; Nagata, Maria Jose Hitomi [UNESP]; Furlaneto, Flávia Aparecida Chaves; Dornelles, Rita de Cassia Martins [UNESP]; Bonfim, Sueli Regina Mogami [UNESP]; Deliberador, Tatiane Miranda; Garcia, Valdir Gouveia [UNESP]; Bosco, Alvaro Francisco [UNESP] (My University, 2011)
Introduction: The urgent need for studies using standardized protocols to evaluate the real biological effects of PRP has been emphasized by several authors. Objective: The purpose of this study was to standardize a methodology for autologous Platelet-Rich Plasma (PRP) preparation in rats. Material and methods: Twentyfour, 5 to 6-month-old, male rats, weighing 450 to 500 g were used. After general anesthesia, 3.15 ml of blood was collected from each animal, via cannulation of the jugular vein. A standardized technique of double centrifugation was used to prepare PRP. PRP samples and peripheral blood platelets were then manually counted using a Neubauer chamber. Student’s t-test was used to compare the differences between the number of platelets in peripheral blood and PRP samples (p < 0.05). In addition, PRP and peripheral blood smears were stained to see platelets’ morphology. Results: All surgical procedures were well tolerated by the animals and they were healthy during the entire experimental period. PRP samples showed higher significantly platelet concentrations than peripheral blood samples (2,677,583 and 683,680 respectively). Conclusion: Within the limits of this study, it can be concluded that the method used produced autologous PRP with appropriated platelet quantity and quality, in rats.
Keywords: Platelet counts; Growth factors; Animal models